"A city in the shadows": The world of bas-fonds (Porto Alegre – mid 1950) - Fagundes, Marluce Dias (Revista Crítica Histórica, 2020)
Crime, addiction and poverty is a triad that can be associated with the dirtiest, lowest, most immoral, devastated, disgusting and despicable part of a city. The understanding of this universe refers to the idea of bas-fonds, which first understood as the places that characterize them: cabarets, rendezvous, hells, spells, tenements as well as prisons and nursing homes. The idea still refers to the individuals who attend and/or live there and are subjected to these scenarios of "horror" of urban life. The central region of the city of Porto Alegre, in the mid-1950s, had its landscape transformed. There is a contrast of light and shadow. As "modernity" advances through the streets of the capital of Rio Grande do Sul, "social and moral decay" invades these same streets. One region, which until nowadays, is present in the social imagination of Porto Alegre is Rua Voluntários da Pátria - recognized as a "red-light zone". To understand this world of bas-fonds we resorted to the analysis of the local press, especially the Daily News, between 1954 and 1960. In addition, the investigation also includes some cases of seductive sexual crimes that reached the police and the Justice.